Geração de resíduos sólidos urbanos e ações de educação ambiental e responsabilidade ética: Floriano-PI - Oliveira, Nívea Gomes Nascimento de (2021)
The inefficiency in the management of Solid Waste (SW) has caused social problems (associated with poverty) and environmental problems (pollution of soil, air and water), with economic impact for society in general. Environmental Education (EE) is the main instrument of change related to the environment. It`s fundamental for the development of critical conscience and it generates civil commitment and ethical responsibility to solve SW related problems, from its generation, going through collection, transportation until final disposal. The present work aims to organize Environmental Education and Ethical Responsibility actions in order to reduce solid waste considering reality in context. The quantity and complexity of urban SW are growing and becoming serious threats to the environment. Isolated actions like collection and disposal do not solve the problem. It is up to Brazilian towns to implement selective collection in their management plans adding the participation of cooperatives and associations formed by low-income people, however there are still few nationwide towns that apply integrated management of SW. Due to the great difficulty in implementing these integrated management models it is up to society as a whole (citizens, governments, private sector and organized civil society) to take responsibility for the environmentally correct management of SW. This policy has worked in some metropolitan cities in the country, such Curitiba-PR. Therefore, EE actions and Ethical Responsibility were implemented in the town of Floriano – PI, as to SW, looking for environmental awareness and the awakening of the community to the importance of integrated and shared management of USW pointing out the importance of Selective Collection, shared responsibility, recycling, sustainable actions and changes that make it possible to reduce USW generation and have correct destination. The participatory descriptive and exploratory observation methodology was applied, aiming to introduce and educate the Floriano community to the importance of reflections and actions to cut down the generation and impacts of urban SW. In a qualitative approach, at first, a historical study of the experience of the management system was carried out, through paper research, to unsderstand the concept of EE adopted by the city of Curitiba-PR. Participant observational activities were carried out during visits to the association and to the cooperative of recyclable material collectors of Curitiba. Secondly, an extension project was developed at the Technical College of Floriano, a federal public school linked to the Federal University of Piauí, with awakening actions and educational practices which are necessary to change paradigms and patterns of production and consumption applicable to an EE system that together with other factors contribute to possible changes. It was observed that the socialization of technical scientific knowledge with a continuous and permanent educational process, such as discussions about the importance of ethical responsibility, contributed to the social and environmental development of the community and to the establishment of an civil environmental awareness. The Environmental Education and Ethical Responsibility actions developed in this work are effective and applicable to any town or city in the country.